Portal vein embolization in the treatment of portal vein bleeding after percutaneous transhepatic biliary drainage: A case report and literature review - Hai Li; Naijian Ge; Chengjian He; Xiangdong Wang; Wei Xu; Jian Huang; Yefa Yang (Journal of Interventional Medicine, 2022)
Percutaneous transhepatic biliary drainage (PTBD) is an effective treatment for benign and malignant obstructive jaundice. Major bleeding complications occur in approximately 2–3% of patients after PTBD, which can result in death. A case involving a 63-year-old male with malignant obstructive jaundice, who experienced severe bleeding after PTBD, is reported. Emergency digital subtraction angiography, celiac trunk artery and superior mesenteric artery angiography were performed; however, no signs of arterial bleeding were found. To identify etiology, portal venography was performed under ultrasound guidance and portal vein bleeding was diagnosed. Ultimately, selective portal vein embolization successfully stopped the bleeding.